PERKAWINAN SALA HURUI PADA MASYARAKAT SUKU DAYAK DI KABUPATEN KATINGAN - Agung Adi (Belom Bahadat, 2020)
Sala hurui marriage is one type of marriage which in principle is strictly prohibited by the Dayak tribe community. But empirically, even though it was banned, this incident still happened as in the research conducted in several villages in Katingan District. Even this prohibition is written down in the form of adat rules or adat law. When this happens it is called manantarang hadat. This research focuses on problems related to the form of sanctions and goals that are accepted for people who to do sala hurui marriage. Theories used to help uncover the problem are the theory of relative criminal and the theory of legal reception. While the data collection method is by interview and document study. While analyzing the data by grouping the data and then doing verification to the conclusion stage. The results of the analysis conducted there are two forms of sanctions in sala hurui marriages namely moral sanctions and traditional rituals sanctions. While the purpose of sanctions is to clean the perpetrators of animalistic qualities and purify again in order to obtain the descent that is expected. In addition, the purpose of other sanctions is to restore the balance of the cosmos.